From Correlation to Context: Evaluating Quantitative Research Practices in Islamic Education - Ana Maryana; Irawan; Ujang Nurjaman (Universitas Nurul Jadid, 2025)
This study aims to identify and describe the methodological characteristics of quantitative research in the field of Islamic Education Management. Using a qualitative descriptive approach and content analysis method, this study analyzes scientific papers in the form of theses, dissertations, and accredited journal articles published between 2020 and 2025. The results of the study show that the quantitative approach in this field is dominated by descriptive and correlational designs, with data collection techniques in the form of questionnaires and simple statistical analyses such as correlation and regression. Although this method offers advantages in terms of objectivity, efficiency, and generalization of findings, its weakness lies in its limitations in exploring the contextual meaning, spiritual values, and complexity of the phenomenon of Islamic education. The study also uncovered key challenges such as inconsistency in instrument validity, gaps between Western methods and Islamic values, and limitations in the use of experimental designs. The implications of this study emphasize the importance of strengthening methodological literacy, the development of contextual instruments based on Islamic values, and the application of more complex quantitative methods to improve the quality of decision-making in Islamic educational institutions. These findings are expected to be the foundation for building an integrative methodological framework in the field of Islamic Education Management.